A Model correlating fluidity to alloy variables in hypoeutectic alloys. (March 2022) - Han, Q.
Abstract: Mechanisms by which flow is choked are described. A criterion function for the choke of flow is proposed based on Darcy's law. Simple mathematical equations are derived to correlate grain size of an alloy to the permeability of its mushy zone, which is a function of the critical volume fraction of solid, gC, at which the flow is choked. Such a correlation gives rise to a simple analytical equation of gC to grain size. A two-parameter equation correlating grain size to phase diagram variables is then used in the analytical equations to describe fluidity as function of alloy variables. Experimental results obtained in well-controlled experiments are used to validate analytical relationships. Model predictions fit experimental data reasonably well. These simple analytical models indicate that fluidity decreases monotonically with increasing solidification interval of an alloy or modified constitutional supercooling parameter which is a function of liquidus slope, partition coefficient, and alloy composition. Graphical abstract: Image, graphical abstract